PENGARUH PERSENTASE PENGAMBILAN VOLUME DISTILAT CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO TERHADAP KARAKTERISTIK CUKA FERMENTASI - Rega Elyana, I Dewa Putu; Ganda Putra, G.P.; Wayan Gunam, I.B. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 3 (2017): September, 2017)
The by-product of fermented cocoa seeds could be fermented into cocoa vinegar. However, the product requires to be distilled to be purified. In this study, an experiment was conducted to determine the percentage in taking the best distillate to produce the best characteristics of cacao vinegar. The percentage was started from 30, 50, 70, and 90% (v/v). The best treatment was determined according to the total acids, acetic acid, total sugars, total soluble solids and pH and distillation time. The result showed that taking distillate volume affected the total acid, acetic acid, and distillation time, and did not affect the total soluble solids, total sugar and pH value. The best distillate preparation of distillate process of cacao vinegar was volume 90% (v/v) with total acid of 0,25 meq NaOH/g, 1,51% acetic acid, pH 2,96, total sugar 0,079%, total soluble solids 1,13oBrix, with a distillation time of 120,25 minutes. Keywords: cocoa, distillation, volume percentage, fermented vinegar